A 64Cu‐porphyrin‐based dual‐modal molecular probe with integrin αvβ3 targeting function for tumour imaging. (6th March 2020) - Fan, Di; Wang, Kai; Gao, Hannan; Luo, Qi; Wang, Xin; Li, Xiaotong; Tong, Wu; Zhang, Xin; Luo, Chuangwei; Yang, Guangjie; Ai, Lin; Shi, Jiyun
Abstract : Pyropheophorbide‐a (Pyro) is a promising multifunctional molecule for multimodal tumour imaging and photodynamic therapy, but its clinical applications are seriously restricted by the limited tumour accumulation capability. Here, we designed and synthesized a small‐molecule probe that achieved specific dual‐modal tumour imaging based on Pyro. Briefly, a novel molecule combining Pyro, an RGD dimer peptide (3PRGD2 ) and 64 Cu, was designed and synthesized, and the obtained molecule, 64 Cu‐Pyro‐3PRGD2, exhibited high tumour specificity in both positron emission tomography and optical imaging in vivo. c (RGDfk) peptide blocking significantly reduced the efficacy of the probe, which confirmed the integrin αV β3 targeting of this molecular probe. 64 Cu‐Pyro‐3PRGD2 had very low accumulation in normal organs and could be rapidly cleared through kidney metabolism, which prevented the potential damage to adjacent normal tissues. Overall, combining tumour targeting, dual‐modal imaging, and biosafety, 64 Cu‐Pyro‐3PRGD2 has the potential for clinical use as a molecular imaging probe for tumour diagnosis. Abstract : Pyropheophorbide‐a (Pyro) is a promising photosensitizer for tumour photodynamictherapy (PDT) and fluorescence imaging. It is also an excellent metal chelator that can form a highly stable 64 Cu‐complexes for PET imaging. However, its clinical applications are seriously restricted by poor water solubility and limited tumour targeting capability. Here, we designed a novel specific dual‐modal imaging molecular probe based on Pyro. The obtained probe 64 Cu‐Pyro‐3PRGD2 has good water solubility and shows high tumour specificity in PET and optical imaging in vivo.